Qur'anic Ethics of Women's Dignity Against Defamation: A Double Movement Hermeneutic Study of Li'an Case in Q.S. An-Nur Verse 6 until 9 - Wathani, Muhammad Fadhil; Maulina, Firdhausa Shafa; Ulum, Syahreza Badarul; Salamah, Ika Hilmiatus; Affandi, Yuyun (QiST: Journal of Quran and Tafseer Studies, 2025)
The protection of women's dignity from baseless accusations remains critical from classical to modern times. This study examines Q.S. An-Nur verses 6-9 concerning li'an using Fazlur Rahman's double movement hermeneutic to uncover ethical principles protecting women's dignity actualized in contemporary contexts. This research aims to analyze Fazlur Rahman's hermeneutic framework, examine classical mufassir interpretations of li'an, and contextualize women's dignity protection through the double movement perspective. Through qualitative literature review, this study employs two movements: understanding the 7th-century patriarchal Arab context and extracting universal moral values for modern challenges. Findings reveal a revolutionary divine intervention, transforming women from accused objects to active legal subjects with equal rights. Five implicit principles emerge: dignity protection ('ird), procedural justice, defamation prevention, nasab protection, and disgrace covering (sitr). These principles address contemporary issues including digital defamation, intimate content distribution, and social media slander through strengthening presumption of innocence, guaranteeing defense rights, protecting privacy, and imposing strict sanctions against false accusations. This research advances ethical Qur'anic interpretation methodology, formulates five previously unarticulated ethical principles, and provides a concrete framework for protecting women's dignity in the digital era, affirming the Qur'an's responsive ethical paradigm across time.